2018
DOI: 10.3390/fib6020021
|View full text |Cite
|
Sign up to set email alerts
|

Routes towards Novel Collagen-Like Biomaterials

Abstract: Collagen plays a major role in providing mechanical support within the extracellular matrix and thus has long been used for various biomedical purposes. Exemplary, it is able to replace damaged tissues without causing adverse reactions in the receiving patient. Today's collagen grafts mostly are made of decellularized and otherwise processed animal tissue and therefore carry the risk of unwanted side effects and limited mechanical strength, which makes them unsuitable for some applications e.g., within tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…Temperature prediction algorithms as a tool for designing heterotrimers will be explored, as well as the use of CMPs to study natural collagen sequences and diseases. Topics such as collagen targeting, , protein interactions with collagen, higher order assemblies of CMPs, collagen biomaterials, ,, and peptide–polymer conjugates have been reviewed recently and are therefore outside the scope of this Perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature prediction algorithms as a tool for designing heterotrimers will be explored, as well as the use of CMPs to study natural collagen sequences and diseases. Topics such as collagen targeting, , protein interactions with collagen, higher order assemblies of CMPs, collagen biomaterials, ,, and peptide–polymer conjugates have been reviewed recently and are therefore outside the scope of this Perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Since many collagen sequences tend to form gels at higher molecular weights, CMP synthesis has been reported to suffer from problems related to limited solubility and aggregation as the molecular weight of the CMP increases. Increasing the molecular weight via chemical ligation has been used to increase the low thermal stability of CMPs but has been shown to reduce the molecular weight homogeneity of the resulting proteins …”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial genomes have been found to contain multiple collagen-like sequences that may have arisen from horizontal gene transfer from eukaryotes to bacteria. Recombinant systems have allowed for the in-depth characterization and manipulation of such bacterial collagen proteins. For example, Streptococcus pyogenes, a Gram-positive bacterium, is known to produce a cell surface collagen-like protein known as Scl2 that may help pathogenic bacteria adhere to animal cells. Sc12 has been found to possess an acidic, highly charged collagen-like (CL) domain that consists of a repeating amino acid triplet Gly–Xaa–Yaa, characteristic of collagen, that is bracketed by an N-terminal assembly domain (V) and a C-terminal transmembrane domain. ,, Notably, the CL domain is highly charged, and in the absence of hydroxyproline, the triple helix structure is stabilized via the formation of intermolecular salt-bridges between charged amino acids. , Subdomains of the Sc12 CL domain have been expressed individually as both homodimers and homotrimers fused with the N-terminal V domain to form stable helical structures, and their stabilities have been found to be dependent upon amino acid composition, sequence lengths, and mutation location in the native sequence. , Various short amino acid sequences derived from human collagen have been successfully inserted into the Sc12 domain such as fibronectin, heparin, and MMPs. It has been previously shown that Sc12 constructs can be expressed in E. coli and purified and that the expressed constructs form stable triple helical structures with a melting temperature ( T m ) of 36–38 °C, close to the stability found in human collagens, , and that these systems can self-assemble into higher-order fibrillar structures .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations